2015
DOI: 10.1096/fj.14-268458
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of alveolar type II cell‐derived cyclooxygenase‐2 to basal airway function, lung inflammation, and lung fibrosis

Abstract: Cyclooxygenase (COX)-2 has been shown to be involved in regulating basal airway function, bacterial LPS-induced airway hyperresponsiveness (AHR) and lung inflammation, and bleomycin-induced lung fibrosis; however, the cellular source of COX-2 that underlies these effects is unknown. We generated mice with alveolar type II (ATII) cell-specific knockdown of COX-2 (AT2CC 2/2 ), to examine the role of ATII cellderived prostaglandins (PGs) in these processes. Specific knockdown of COX-2 was confirmed by real-time R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…Findings that it remained elevated for at least 21 d are in accord with the persistent inflammatory response observed in exposed humans (Yoon et al, 2013; Liu et al, 2015). The fact that COX-2 was mainly expressed by Type II cells provides support for the notion that these cells participate in inflammatory responses to tissue injury (Cheng et al, 2016). IL-6RA1 mRNA was also upregulated in the lung 21 d post-WTC dust exposure.…”
Section: Discussionmentioning
confidence: 65%
“…Findings that it remained elevated for at least 21 d are in accord with the persistent inflammatory response observed in exposed humans (Yoon et al, 2013; Liu et al, 2015). The fact that COX-2 was mainly expressed by Type II cells provides support for the notion that these cells participate in inflammatory responses to tissue injury (Cheng et al, 2016). IL-6RA1 mRNA was also upregulated in the lung 21 d post-WTC dust exposure.…”
Section: Discussionmentioning
confidence: 65%
“…We therefore hypothesize that these mechanisms by themselves are not sufficient to counteract the LPS-induced injury completely. Nonetheless, prostanoids produced from alveolar epithelial cells are protective, as a recent paper addressing acute lung injury in ATII-cell-specific COX-2 knockout mice reported increased levels of neutrophils and total cell counts in the bronchoalveolar lavage-fluid 49 and aggravated overall inflammation. Together with the fact that PGE 2 via EP4 receptor stimulation inhibits inflammation and neutrophil influx 20 , 50 , 51 , we provide further evidence that PGE 2 synthesized via the COX-2 pathway in ATII cells acts as an anti-inflammatory mediator.…”
Section: Discussionmentioning
confidence: 99%
“…The EVs are enriched for several miRNAs, including miR-630, which targets the pro-fibrotic genes that are upregulated in IPF fibroblasts. They also reported that administration of human MSC-derived EVs at day 14 in mice with pulmonary fibrosis induced by bleomycin significantly downregulated α-smooth muscle actin expression and decreased histopathological fibrosis, indicating the therapeutic effects of these vesicles on the established lung fibrosis through modification of the myofibroblastic phenotype [ 81 ].…”
Section: Mesenchymal Stem Cell-derived Extracellular Vesicle-basedmentioning
confidence: 99%